Financial distress situation of financial sectors in Ethiopia: A review paper - Esmael Abdu (Cogent Economics & Finance, 2022)
The development of financial sectors is considered as one of vital determinants of the growth of Ethiopian economy, and for secure equitable distribution of the benefits to the society. However, financial distress has an effect on the sectors. This review was conducted to assess financial distress situation of financial sectors in Ethiopia. The objective is specifically to identify the determinants of financial distress, opportunities of financial sectors, and challenges and constraints of financial distress in Ethiopia. Ethiopia is a developing country with majority of unbanked population. Liquidity, profitability, leverage, firm size, capital adequacy, management efficiency, earning ability, inflation and interest rate are major determinant of financial distress in Ethiopia. Moreover, Ethiopian financial sectors have an opportunity of trade openness, rapid economic growth, unexploited resource, population growth and encouragement of privatization.
Keywords: 330; Commercial banks; Companies; Financial distress; Insurance; Microfinance